1922
DOI: 10.1152/ajplegacy.1922.59.1.310
|View full text |Cite
|
Sign up to set email alerts
|

Some Plant Sources of Vitamins B and C

Abstract: In the problem of food selection, instinct is considered by many persons to be a fairly safe guide. Therefore it is often assumed that the question of vitamin deficiency in the diet needs no special consideration. 478655 UNIVERSITY OF CALIFORNIA LIBRARY UNIVERSITY OF CALIFORNIA LIBRARY, BERKELEY THIS BOOK IS DUE ON THE LAST DATE STAMPED BELOW Books not returned on time are subject to a fine of 50e per volume after the third day overdue, increasing to $1.00 per volume after the sixth day. Books not in demand ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1927
1927
1983
1983

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Among the earlier workers in this field were Chick and Delf (1919), who reported that germinated peas and lentils showed a higher anti-scorbutic value than did the dry seeds and, a little later, Santos (1922) stated that the vitamin B content of mung beans was enhanced by sprouting. Other tests with various legumes have indicated that germination results in an increase in vitamin C, Rose and Phipard (1937), or in vitamin B, C'heldelin and Lane (1943), or in both of these vitamins or vitamin groups, Burkholder and RlcVeigh (1945).…”
mentioning
confidence: 99%
“…Among the earlier workers in this field were Chick and Delf (1919), who reported that germinated peas and lentils showed a higher anti-scorbutic value than did the dry seeds and, a little later, Santos (1922) stated that the vitamin B content of mung beans was enhanced by sprouting. Other tests with various legumes have indicated that germination results in an increase in vitamin C, Rose and Phipard (1937), or in vitamin B, C'heldelin and Lane (1943), or in both of these vitamins or vitamin groups, Burkholder and RlcVeigh (1945).…”
mentioning
confidence: 99%